2004
DOI: 10.1099/mic.0.27291-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and occurrence of tetrad-forming Alphaproteobacteria in anaerobic–aerobic activated sludge processes

Abstract: In an acetate-fed anaerobic-aerobic membrane bioreactor, a deteriorated enhanced biological phosphorus removal (EBPR) community was developed (as determined based on the chemical profiles of organic substrate, soluble phosphate, and intracellular carbohydrate and polyhydroxyalkanote (PHA) concentrations). Microscopic observations revealed the dominance of tetrad-forming organisms (TFOs), of which the majority stained positively for PHA under anaerobic conditions. Fluorescence in situ hybridization (FISH) confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
1
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(199 citation statements)
references
References 42 publications
5
192
1
1
Order By: Relevance
“…DF2MIX (Table 1) Defluvicoccus-related organisms accounted for an additional 8 % (SEM=1 %) of the Bacteria, and the cells that bound these probes were TFOs. The fact that the majority of Alphaproteobacteria in the biomass that cycled PHA did not bind the current probes for GAOs strongly suggests the presence of other GAOs, despite the similar morphology of these organisms to those described in the literature (Beer et al, 2004;Meyer et al, 2006;Wong et al, 2004). It may be that the probes from these publications do not target the diversity of the organisms within these already identified groups so that additional sequences are required in order to broaden the probe specificities; alternatively, another group of GAOs unrelated to Sphingomonas or D. vanus may exist.…”
Section: Fish and Post-fish Chemical Stainingmentioning
confidence: 90%
See 1 more Smart Citation
“…DF2MIX (Table 1) Defluvicoccus-related organisms accounted for an additional 8 % (SEM=1 %) of the Bacteria, and the cells that bound these probes were TFOs. The fact that the majority of Alphaproteobacteria in the biomass that cycled PHA did not bind the current probes for GAOs strongly suggests the presence of other GAOs, despite the similar morphology of these organisms to those described in the literature (Beer et al, 2004;Meyer et al, 2006;Wong et al, 2004). It may be that the probes from these publications do not target the diversity of the organisms within these already identified groups so that additional sequences are required in order to broaden the probe specificities; alternatively, another group of GAOs unrelated to Sphingomonas or D. vanus may exist.…”
Section: Fish and Post-fish Chemical Stainingmentioning
confidence: 90%
“…One group are members of the order Sphingomonadales, and the other is related to the isolate Defluvicoccus vanus within the order Rhodospirillales. Both of these organisms could consume acetate as the sole carbon source (Beer et al, 2004;Wong et al, 2004), but the D. vanus-related organism has also been recently demonstrated to consume propionate (Meyer et al, 2006), unlike Competibacter.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster 1 Defluviicoccus always constituted <1 % of Bacteria in plants surveyed here. Previous surveys of full-scale plants from several countries (Wong et al, 2004(Wong et al, , 2005) also demonstrated low numbers of Cluster Not included 2 h anaerobic 2 1C. Anaerobic 3 h anaerobic; 1.5 mM unlabelled acetate added at t=0 2 h anaerobic +/2 1D.…”
Section: Resultsmentioning
confidence: 99%
“…FISH probes used in this study were NON338 for non-specific binding (Wallner et al, 1993), EUBMIX for Bacteria (Amann et al, 1990;Daims et al, 1999), DF1MIX (TFO_DF218 plus TFO_DF618) for the Alphaproteobacteria from Cluster 1 Defluviicoccus spp. (Wong et al, 2004), DF2MIX (DF988, DF1020 plus helper probes H966 and H1038) for Cluster 2 Defluviicoccus spp. (Meyer et al, 2006), SBR9-1a for Alphaproteobacteria Sphingomonas spp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation